PERAN ORANG TUA MUALLAF DALAM MENANAMKAN NILAI PENDIDIKAN AGAMA ISLAM PADA ANAK DI DESA AIR SEMPIANG KEPAHIANG - Karliana; Sulis Vera Dilla; Rosella Agustina; Heri Sakyan; Sintia Marsita (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research is motivated by the role of parents of converts in increasing understanding of the values ​​of Islamic religious teachings which is very lacking, and will have a big influence on children's education, especially Islamic religious education, where this directly influences the behavior and development of children wherever they are, not only in home but has an influence in the community, school and other environments. This research aims to find out the role of convert parents in instilling Islamic teaching values ​​in children in Air Sempiang Kepahiang Village. The method used in this research is the qualitative descriptive method or field research. Data collection uses observation, interviews and documentation. Data validity techniques use Source Triangulation, Technique Triangulation, Time Triangulation. The subjects in this research were parents of converts and children. Based on the analysis of the results of this research, it shows that the role of parents of converts in instilling the values ​​of Islamic teachings in their children varies, some are said to be successful and some are not said to be successful. it is said to be successful, here the convert's parents have clear educational goals, the aim of which is for the child to become an obedient person and has known the understanding of the teachings of Islam since childhood so that the child becomes a guide to life in the future, whereas those who have not yet been said to be successful Here, the most important thing is that children become good people towards their parents and other people in the surrounding community, not directing them towards the religion they currently adhere to. The conclusion in this case is that the role of parents towards children is mostly only for those who have not yet developed an understanding of Islamic religious values. to their children, but there are also some parents who are converts to Islam who provide religious understanding to their children using various methods with the aim of encouraging the children to perform prayers.